2022
DOI: 10.1016/j.jtho.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Study of Dabrafenib Plus Trametinib in Patients With BRAF V600E-Mutant Metastatic NSCLC: Updated 5-Year Survival Rates and Genomic Analysis

Abstract: and reports receiving grants from Eli Lilly and Bristol-Myers Squibb. Zhang reports employment for Novartis. Tan reports employment for Novartis. Gasal reports employment for Novartis. Santarpia reports employment for Novartis. Dr. Johnson reports receiving grants from Cannon Medical Systems, grants and personal fees from Novartis, and personal fees from Hengrui Therapeutics, Daiichi Sankyo, Checkpoint Therapeutics, Lilly, and G1 Therapeutics; has a patent EGFR Mutation Testing with royalties. Hashemi declares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 40 publications
1
127
1
1
Order By: Relevance
“…In BRAF mutant malignancies, treatment with BRAF inhibitors lead to amplification or activating of mutations that restore downstream MAPK signaling [ 65 ]. In NSCLC, adding a downstream MEK inhibitor to BRAF inhibitors improved duration of responses from 6.3 months to 10.2 months [ 26 , 66 ].…”
Section: Drug Resistancementioning
confidence: 99%
“…In BRAF mutant malignancies, treatment with BRAF inhibitors lead to amplification or activating of mutations that restore downstream MAPK signaling [ 65 ]. In NSCLC, adding a downstream MEK inhibitor to BRAF inhibitors improved duration of responses from 6.3 months to 10.2 months [ 26 , 66 ].…”
Section: Drug Resistancementioning
confidence: 99%
“…Dabrafenib and trametinib are inhibitors of BRAF and MEK, respectively, and their combination (dabrafenib plus trametinib [dab-tram]) is the only approved treatment for patients with BRAF V600 -mutated aNSCLC. 16 , 17 , 18 , 19 The clinical utility of dab-tram in BRAF V600E -mutated aNSCLC has been revealed in a noncomparative open-label, phase 2 trial, which reported overall response rates of 64% in treatment-naive patients, 20 and 63.2% in pretreated patients, 21 with a median overall survival (OS) of 17.3 months and 18.2 months, 22 respectively. Dab-tram was well tolerated and had a safety profile similar to that previously reported in patients with BRAF V600 -mutant metastatic melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, in 2017, the Food and Drug Administration approved dabrafenib and trametinib for first-line treatment of metastatic NSCLC patients harboring BRAF V600E mutation. The update of a phase 2 study (NCT01336634) showed promising efficacy of dabrafenib plus trametinib as second-line treatment, with a median PFS of 10.2 months and a median OS of 18.2 months [ 23 ] . However, no clinical trial has been conducted to confirm the efficacy of EGFR/BRAF/MEK co-inhibition in patients harboring E19 and BRAF V600E after the therapy of osimertinib.…”
Section: Discussionmentioning
confidence: 99%